Sarah Walkley. Cultural Diversity in the French Film Industry: Defending the Cultural Exception in a Digital Age. Palgrave MacMillan. - Anna V Keefe (Studies in 20th & 21st Century Literature, 2019)
Review of Sarah Walkley, Cultural Diversity in the French Film Industry: Defending the Cultural Exception in a Digital Age. Palgrave MacMillan, 2018.
Keywords: cultural exception; cultural diversity; French film policy; trade negotiations; digital